Can Sleeve Gastrectomy "Cure" Diabetes? Long-term Metabolic Effects of Sleeve Gastrectomy in Patients With Type 2 Diabetes. Issue 4 (October 2016) - Aminian, Ali; Brethauer, Stacy A.; Andalib, Amin; Punchai, Suriya; Mackey, Jennifer; Rodriguez, John; Rogula, Tomasz; Kroh, Matthew; Schauer, Philip R.
Abstract : Objective: The aim of the study was to assess long-term metabolic effects of laparoscopic sleeve gastrectomy (LSG) in patients with type 2 diabetes (T2DM) and to identify predictive factors for long-term diabetes remission and relapse. Background: LSG has become the most common bariatric operation worldwide. Its long-term metabolic effects in patients with T2DM are, however, unknown. Methods: Outcomes of 134 patients with obesity with T2DM who underwent LSG at an academic center during 2005 to 2010 and had at least 5 years of follow-up were assessed. Results: At a median postsurgical follow-up of 6 years (range: 5–9), a mean body mass index loss of −7.8 ± 5.1 kg/m 2 (total weight loss: 16.8% ± 9.7%) was associated with a reduction in mean glycated hemoglobin (HbA1c, −1.3 ± 1.8%, P < 0.001), fasting blood glucose (−37.8 ± 70.4 mg/dL, P < 0.001) and median number of diabetes medications (−1, P < 0.001). Long-term glycemic control (HbA1c <7%) was seen in 63% of patients (vs 31% at baseline, P < 0.001), diabetes remission (HbA1c <6.5% off medications) in 26%, complete remission (HbA1c <6% off medications) in 11%, and "cure" (continuous complete remission for ≥5 years) was achieved in 3%. Long-term relapse of T2DM after initial remission occurred in 44%. Among patients with relapse, 67% maintained glycemic control (HbA1c <7%). On adjusted analysis, taking 2 or more diabetes medications at baseline predicted less long-term remission (odds ratio 0.19, 95% confidence interval 0.07–0.55, P = 0.002) and more relapse of T2DM (odds ratio 8.50, 95% confidence interval: 1.40–49.20, P = 0.02). Significant improvement in triglycerides (−53.7 ± 116.4 mg/dL, P < 0.001), high-density lipoprotein (8.2 ± 12.9 mg/dL, P < 0.001), systolic (−8.9 ± 18.7 mmHg, P < 0.001) and diastolic blood pressure (−2.6 ± 14.5 mmHg, P = 0.04), and cardiovascular risk (13% relative reduction, P < 0.001) was observed. Conclusions: LSG can significantly improve cardiometabolic risk factors including glycemic status in T2DM. Long-term complete remission and "cure" of T2DM, however, occur infrequently.